Child Medical & Health Advisor (CMHA) / Anbarasan Palasubramaniam - Anbarasan, Palasubramaniam (2003)
The Child Medical & Health Advisor (CMHA) is a stand-alone system that incorporates the design structure of an expert system. It has a knowledge base, an inference engine and the interface. The system is developed to serve the purpose as a system that provides information on child health issues. These issues are child illness, sickness care, treatment and home care. The system also provides a diagnostic capabilities to the user. It's able to provide diagnosis up to 30 diseases. The system is designed using forward chaining control strategy and having rules as its knowledge base. The knowledge was acquired from medical books on child health and the system was developed using Visual Basic v6.0. This system could be installed in a personal computer using windows operating software version 98 and above.